Unregulated miR-96 Induces Cell Proliferation in Human Breast Cancer by Downregulating Transcriptional Factor FOXO3a - Lin, Huanxin (Public Library of Science, 2010)
FOXO transcription factors are key tumor suppressors in mammalian cells. Until now, suppression of FOXOs in cancer cells was thought to be mainly due to activation of multiple onco-kinases by a phosphorylation-ubiquitylation-mediated cascade. Therefore, it was speculated that inhibition of FOXO proteins would naturally occur through a multiple step post-translational process. However, whether cancer cells may downregulate FOXO protein via an alternative regulatory mechanism is unclear. In the current study, we report that expression of miR-96 was markedly upregulated in breast cancer cells and breast cancer tissues compared with normal breast epithelial cells (NBEC) and normal breast tissues. Ectopic expression of miR-96 induced the proliferation and anchorage-independent growth of breast cancer cells, while inhibition of miR-96 reduced this effect. Furthermore, upregulation of miR-96 in breast cancer cells resulted in modulation of their entry into the G1/S transitional phase, which was caused by downregulation of cyclin-dependent kinase (CDK) inhibitors, p27(Kip1) and p21(Cip1), and upregulation of the cell-cycle regulator cyclin D1. Moreover, we demonstrated that miR-96 downregulated FOXO3a expression by directly targeting the FOXO3a 3′-untranslated region. Taken together, our results suggest that miR-96 may play an important role in promoting proliferation of human breast cancer cells and present a novel mechanism of miRNA-mediated direct suppression of FOXO3a expression in cancer cells.